Variability of dynamic 18F-FDG-PET data in breast cancer xenografts. (21st October 2015) - Pitman, Kathinka E.; Rusten, Espen; Kristian, Alexandr; Malinen, Eirik
ABSTRACT: Background. A murine breast cancer xenograft model was employed to evaluate inter- and intra-variability of various parameters derived from dynamic positron emission tomography with [18F]-fluorodeoxyglucose as tracer (FDG-PET). Material and methods. Seventeen female athymic nude foxn1/nu mice with bilaterally implanted triple-negative basal-like ductal carcinoma (MAS98.12) breast cancer xenografts underwent a dynamic PET scan over an hour after injection of approximately 10 MBq FDG. Inter-animal data were obtained from the entire animal cohort, while intra-animal data were from four mice receiving an additional scan after one or two days. Standardised uptake values (SUVmax, SUVmean and SUVmedian ) were estimated for all tumours at different time points. Tumour uptake was analysed with a kinetic two-compartment model for estimation of pharmacokinetic parameters. The coefficient of variation (CV) was calculated for all PET-derived metrics. Results. The CVs for SUVmean and SUVmedian were typically 10–20% for the tumours, depending on the time post-injection and group (intra vs. inter). The CV for SUVmax was mostly higher. The variability in the pharmacokinetic parameters ranged from 23 to almost 150%. Conclusions. SUVmean and SUVmedian show less variability than SUVmax . The pharmacokinetic tumour metrics again display much greater variability than the SUV-based metrics. However, it is generally not known which of these metrics that best represents cancer aggressiveness and their use may still depend on the research questions addressed.